Becoming in Resistance: The (Un)Creative Relation Between Non-heterosexual Identity and Psychological Suffering - Collado, Sebastián; Besoain, Carolina (Frontiers in Psychology, 2020)
This article aims at theorizing a creative and processual theory of non-heterosexual identity. It will be argued that, so far, scholars have tended to theorize non-heterosexual identity from a monologic perspective, which establishes one-sidedly a casual and/or unproblematic relation between the emergence of forms of psychological suffering and the development of a non-heterosexual identity. Although it must be recognized that such a claim is important at a political level, at a subjective level, it leaves non-heterosexual people destined to be flooded by distressing and painful emotional states. To counter monologism within theorisations of non-heterosexual identity development, without ignoring the negative impacts of heteronormativity, it will be argued that non-heterosexual identity needs to be theorized 1) as part of a creative process situated in a specific sociohistorical context marked by heteronormativity, 2) as part of a situated process that produces and never ceases to produce multiple effects (self-states), which are unified to create an identity, and 3) as part of a situated process of creation that can be artificially transformed through art. These are the three claims that will move forward the argument of this article.